FACTORS INFLUENCING THE CHANGING OF BELIEF AND FUNERAL RITUAL OF LANNA - ชัยวงศ์, ศิลาวัฒน์ (Journal of MCU Social Science Review, 2020)
This article is part of the research topic is factors influencing in the beliefs and rite of the funeral of Lanna people. The objective of the research have three point, first to study the development of the beliefs and rite of the funeral of Lanna people, second to study the factors that influence the beliefs and rite of the funeral of Lanna rite people and third to analyze trends, changes in the beliefs and rite of the funeral of Lanna people. The study found that the development of the beliefs and rite of the funeral is the funeral rites of Lanna that combines Buddhism, Brahmanism and the superstition. The funeral rites of general of Lanna people when someone died in my house, it is relative including to People in the community to express their roles. Towards the victim based on Buddhism. Moreover the funeral rites are different according to the nature of death. Lanna people have 2 case, Dead and Evil Dead the funeral rites of the Lanna people have many step carefully, like a cleaning body victim, the hair making and cremation. Moreover, Lanna also have faith in the funeral rites that are characteristic of the local casket and cremation. Such beliefs Hastilinga, Belief in the castle. And beliefs about the Huan Yen. In this research also has found the change of the funeral rites of Lanna people is Factors that influence the beliefs and rite of the funeral of Lanna people. Factors such as the social,cultural is complementary nature of the help of the community or village was changed into a trade and business of funeral, The economic factor is the capitalist economy is Influence ceremonial funerals because funerals are reflecting the financial position of the deceased. So the economy is a importance in the funeral rites, finally factor of politics and government is the funeral rites imports from outside and the realization of the changes in the funeral rites of Lanna people by leader. In addition to changing trends for beliefs and rite, funerals of Lanna people are three reasons, first the ritual of the funeral of the Lanna people under capitalism. Now rite funeral has been linked to a capitalist economy by the looks of it, do not aim for a memorial to the dead, but is only a matter of business involved, second the funeral rites changes from the past to the present is Currently, the funeral rites have been interpreted and practices are very different from the original. Originally a traditional Lanna rite of the dead simple procedure with small ceremony. But the current emphasis on formalities and procedures are costly, third Book memories cremation concept does not appear in the Lanna people.